P789 Symptom burden and lack of remission among adult patients with ulcerative colitis (UC): retrospective analysis of cross-sectional survey data from the US and Germany. (25th January 2019) - Gorsh, B; Bracher, M; Symons, J M; Nafees, B; Chauhan, D; Hoskin, B; Lucas, J; Kershaw, J; Middleton, C
Abstract: Background: Patients with UC experience a wide range of debilitating symptoms covering bowel and abdominal manifestations with a significant impact on health-related quality of life. This study used data from the Adelphi Disease-specific Programme (DSP), a large, cross-sectional survey, to describe the burden of UC in a real-world setting in the US and Germany (DE). Methods: This study is a retrospective, descriptive analysis of data collected from patients consulting for routine care in the US and Germany during Q4 2017. As part of the survey, patients and physicians were asked to report the symptoms currently experienced by the patient. Patient satisfaction with treatment, disease severity, and disease progression were captured along with current and prior treatment use. 1 Results: Physician-reported symptoms data were collected from 1123 UC patients by 100 physicians across US and Germany. A voluntary subset of the sample provided patient-reported data which included 270 (US)/303 (DE) patients used for this analysis. In the overall sample, patients had a mean age: 42.7 (US)/35.2 (DE) and disease duration since diagnosis of 3.7 (US)/2.9 (DE) years. 30.3% (US)/22.3% (DE)of patients were receiving biologics at the time of the survey. At diagnosis, 88.3% (US)/91.5% (DE) of patients were considered to have moderate to severe disease per physician decreasing to 50.1% (US)/47.9 (DE) at the time of the survey. Patients reported the most common current and most bothersome symptoms to be abdominal cramps and pain, diarrhoea, tiredness/fatigue and rectal bleeding (Table 1). Despite improvements in disease severity, 50.9% (US)/39.6% (DE) of patients were not in remission with only 6.7% (US)/7.1% (DE) achieving clinical remission as reported by the physician. Interestingly, 87.2% (US) / 90.6% (DE) of patients expressed satisfaction at the extent to which their current treatment was able to manage the disease with 58.1% (US)/ 63.6% (DE) believing that this is the best control that can be achieved. Conclusions: In a real-world setting, patients show a physician assessed improvement in disease severity from the time of diagnosis to present day with a relatively high patient-reported satisfaction rate. However, patients continue to experience numerous symptoms related to UC and have difficulty reaching remission, with only a small proportion of the patients achieving clinical remission as reported by physicians, suggesting that with currently available treatment patients do not expect to have complete resolution of symptoms. Reference 1. Anderson P, Benford M, Harris N, et al. Real-world physician and patient behaviour across countries: disease-specific programmes - a means to understand. Curr Med Res Opin 2008;24:3063–72.